(untitled) (American Journal of Business Management, Economics and Banking, 2024)
This article discusses the economic nature of the global financial market, its social features and its theoretical and methodological aspects, its main and additional functions and principles, the implementation of market instruments, and is scientifically based from the perspective of participating institutions. to perform the functions of its peculiarities.